Faktor Yang Berperan Terhadap Pola Menyusui Secara Eksklusif Pada Pasien Setelah Rawat Gabung Di RSUP DR.Sardjito - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1994)
To examine the risk factors of exclusive breastfeeding after rooming in at Sardjito Hospital. Observational study had been done among women who delivered their babies at Sardjito Hospital from February to April 1992. One hundred women, as study subject were randomly selected from all women who delivered their babies in those period. The women were followed up for 4 months after discharged from the hospital. The association of potential determinants with exclusilie breastfeeding were examined using bivariat, stratification, and multivariat analysis. Only 44% mothers exclusively breastfeeding their newbom babies. The working mothers were significantly increasing the risk of non exclustve breastfeeding (p